The History of International Cooperation and Integrations in East Central Europe - Lys´ý, Miroslav (Lectures on East Central European Legal History, 2023)
The chapter deals with the development of international relations, international cooperation and international law in central Europe since the beginning of Middle Ages until present times. The topic exceeds as far as to the relation between international and constitutional law. While we could characterize the first centuries of the Middle Ages as a struggle between imperial universalism (Frankish empire, German-Roman empire), since 12th century it was the particularism of central European countries like Poland and Hungary (and the particularism within German-Roman empire) that set pace. Various particular units, however, often integrated into larger unions, united as personal or (later) real unions. In case of Hungary and Czech lands, the idea of Crown lands was created in order to express the unity of various countries with a different level of integration. Amongmany unions it was the case of Habsburg empire that proved itself as very successful and viable and lead across many unifying attempts into the Austrian-Hungarian compromise of 1867. Dualistic statehood lasted half a century and after the World War I it was replaced by new organized central Europe, with new states, new borders and new system of international security. The character of Versailles Peace, however, resulted in new controversies and new hostile relations during late 1930s. After Anschluß of Austria and especially the Munich treaty (1938), the Versailles system in central Europe was definitively gone. A new order was set after the end of World War II, when central Europe had become a part of the Soviet bloc. This lasted until 1989, when the Soviet-controlled regimes in Central Europe ceased to exist and Central Europe started to integrate with the structures of the European Union and NATO. KEYWORDS: history of Central Europe, integration, personal